2016
DOI: 10.1016/j.ebiom.2015.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Blood Thiamine Metabolites for Alzheimer's Disease Diagnosis

Abstract: BackgroundBrain glucose hypometabolism is an invariant feature and has significant diagnostic value for Alzheimer's disease. Thiamine diphosphate (TDP) is a critical coenzyme for glucose metabolism and significantly reduced in brain and blood samples of patients with Alzheimer's disease (AD).AimsTo explore the diagnostic value of the measurement of blood thiamine metabolites for AD.MethodsBlood TDP, thiamine monophosphate, and thiamine levels were detected using high performance liquid chromatography (HPLC). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 36 publications
7
58
1
1
Order By: Relevance
“…Both the TDP level and the activity of TDP-dependent enzymes are significantly reduced in blood and brain autopsy samples from AD patients [7][8][9]. Our previous study showed that TDP reduction is a significant biomarker for AD diagnosis [10]. The reduction of brain glucose metabolism and its possible pathogenic indicator, TDP reduction, implicate multiple pathogenic pathways in AD, including oxidative stress [11], neuroinflammation [12], and enhanced activity of glycogen synthase kinase-3 [13] and b-secretase [14].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Both the TDP level and the activity of TDP-dependent enzymes are significantly reduced in blood and brain autopsy samples from AD patients [7][8][9]. Our previous study showed that TDP reduction is a significant biomarker for AD diagnosis [10]. The reduction of brain glucose metabolism and its possible pathogenic indicator, TDP reduction, implicate multiple pathogenic pathways in AD, including oxidative stress [11], neuroinflammation [12], and enhanced activity of glycogen synthase kinase-3 [13] and b-secretase [14].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Both TDP level[8,9,10,11] and activities of TDP-dependent enzymes[12,13,14,15] have been demonstrated to be significantly decreased in AD. Previous studies have demonstrated that thiamine deficiency can induce or aggravate AD-like pathologies, such as neuritic plaques, and hyperphosphorylation of tau, finally memory deficits[16].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is evidence of age-related differences [15]. The elderly (>76 years of age) are known to have a reduced total thiamine compound concentration that can be 21%-26% lower than that of the middle aged [57,137]. A longitudinal study of over 300 participants spanning 3 years by Wilkinson et al [15] examined a younger, healthy population (mean age 41.5 years) of 100 volunteers and compared it to an elderly population (mean age 76 years) of 221 participants.…”
Section: Post-analyticalmentioning
confidence: 99%
“…Its involvement in these metabolic pathways and its intracellular abundance has made TPP a popular analyte for assessing thiamine status. However, there are also proposed non-cofactor roles of thiamine compounds within the immune system, gene regulation, oxidative stress response, cholinergic activity, chloride channels and neurotransmission [8,[56][57][58][59][60][61].…”
Section: Physiology Of Thiaminementioning
confidence: 99%